ORGANISATION AND OPTIMISATION OF PROCUREMENT FOR MILITARY UNITS OF THE NATIONAL GUARD OF UKRAINE UNDER MARTIAL LAW: REGULATORY, FINANCIAL AND ANTI-CORRUPTION ASPECTS - Fedorenko, Irina; Naumenko, Mariia (Honor and Law, 2025)
The article provides a comprehensive study of the peculiarities of organizing and optimizing procurement for the military units of the National Guard of Ukraine under martial law conditions. The research focuses on three key aspects: legal and regulatory support, financial mechanisms, and anti-corruption measures in the field of defense procurement. A Procurement Corruption Risk Index (PCRI) is proposed, which allows for a quantitative assessment of the risk level associated with the use of simplified procedures. A multi-criteria model for selecting the organizational procurement model has been developed based on the Analytic Hierarchy Process (AHP), taking into account criteria such as cost, delivery speed, and the level of corruption risks. An important result of the study is an economic-mathematical model for optimizing financial support, which demonstrates that international assistance can compensate for up to 30 % of the state funding deficit. A formula for calculating the total procurement cost is proposed, integrating not only direct expenses but also risk-related losses from market instability and disruptions in the logistics chain. The study identifies optimal directions for optimizing procurement processes, including a combination of centralized and decentralized models, the implementation of digital solutions, standardization of requirements, and strengthening preventive anti-corruption control.